Our country, the planet: foraging a partnership for survival - Ramphal, Shridath (Island P. WashingtonUS, 1992)
Calls for restraint by the North in global pollution and makes a plea for the North to rescue the South from poverty. Proposes a multilateral programme comparable to the Marshall Plan. Posits that we need to see the whole world as our country, as the integral land whose fortunes and whose future are our own.